IMPOSITION OF MORTGAGE RIGHTS BY THE GRANTOR OF THE GRANT BINDING AGREEMENT OBJECT - KARNILLA; AHMADI MIRU; WINNER SITORUS (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
This paper analyzes the object of the grant binding agreement made in the presence of a notary public who can be liable to a third party by the granter This study uses a normative juridical approach, namely legal writing done by examining data or library materials which are secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. After the legal materials are collected, they are processed and analyzed using qualitative methods. The research results show that basically, the agreements that have been made based on the provisions of Article 1320 Burgerlijk Wetboek have binding legal force, meaning that the agreements that have been approved and set forth in the form of a binding agreement are laws for those who make them. Therefore, the grant binding agreement made before a notary public even though there has been no transfer of title to land, the object of the grant binding agreement cannot be borne by the grantee to a third party, given the initial purpose of making the agreement deed of the grant agreement is so that real grants can be made.